DEVELOPMENT OF SPECIALIZED SOFTWARE FOR INCREASING THE EFFICIENCY OF SCIENTIFIC RESEARCH IN VOCATIONAL EDUCATION - Klopov, Roman; Pshenichnaya, Elena (Continuing Professional Education: Theory and Practice, 2019)
The presented article focuses on the issues, related to usage of contemporary information technologies when conducting research in the field of professional education. The conducted analysis proves the relevance of this issue to the present day research paradigm and proves the fact that there are a number of approaches to its resolution. The latter include standard software applications, internet technologies and custom software. Background research has outlined the perspectives implementing specialized software in conducting pedagogical experiment. The article features the programme «RTEST», designed to evaluate the readiness of the Sports Department students of the to use information technologies in their professional activity. The presented software product has been successfully implemented to assess the readiness of future specialists in sports to use information technologies, basing on their integral index of readiness. This in its turn enables minimal statistical processing of the individual and group results, obtained during the experiment. The article also features the dialogue system “Choosing the criterion”, designed to choose the effective method of mathematical statistics and enabling adequate mathematical processing. The results obtained prove the efficiency of implementing various systems at different stages of pedagogical research. Consequently, the authors facilitate the necessity to include the course «Statistics Methods of Data Processing in Pedagogical Experiment» into the curriculum of future Philosophy Doctors in Education. The article substantiates the necessity to include into the syllabus the thematic courses related to technical assignment in developing pedagogical software.